(untitled) (Research, Society and Development, 2021)
Objective: to identify the nurse’s conduct when attending a pregnant woman with HIV Methodology: this is an integrative review of a qualitative approach, with the researches carried out in the online database of the Regional Portal of the Virtual Health Library (VHL) and in its affiliated sites. Publications published between 2011 and 2019 were included, with full text, articles, monographs and theses in Portuguese and English, available free of charge, covering up to three used descriptors. Works with a date lower than 2011 were excluded, also those that presented only abstracts and citations with languages other than those previously mentioned. The study consisted of an analysis of 10 publications. Results: It is essential to the assistance and guidance of nurses on preventing risks and problems, not needing to limit clinical-obstetric actions, and adding health education actions as a usual practice of comprehensive care. Thus, nurses’ skills throughout prenatal care for HIV-positive women stand out in educational methods for HIV prevention in the face of the mother / child binomial. Conclusion: it was noticed that HIV infection in recent years has been growing, and nurses have a very important role in Primary Health Care (PHC) because it has contributed a lot to reduce the transmission of this virus in HIV-positive pregnant women.